PECULIARITIES OF CONTROL OVER ENSURING THE STABILITY OF TAX REVENUES TO THE STATE BUDGET - Rustamov Shohruh Shuhratovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article delves into the unique characteristics and challenges associated with the oversight of tax revenue stability in state budgets. It examines the various mechanisms of control employed by governmental bodies to ensure consistent and reliable tax income, which is crucial for fiscal health and public service financing. The analysis highlights the interplay between tax policy, economic fluctuations, and enforcement measures, elucidating how these factors influence revenue predictability. Furthermore, the article explores innovative approaches and best practices in revenue stabilization, assessing their efficacy in different economic contexts. By investigating contemporary strategies and potential reforms, the article aims to provide insights for policymakers seeking to enhance the resilience of tax systems in the face of economic uncertainties. Through this exploration, it offers a comprehensive perspective on maintaining fiscal sustainability and the importance of adaptive control measures in tax administration.